Balancing fertility and livelihood diversity in mixed economies. - Joseph V Hackman (Public Library of Science (PLoS), 2021)
Mixed economies provide a unique context for testing theories of fertility change. Because they have a stake in two traditions, mixed-economy households balance the demands of both a labor-based subsistence economy, which benefits from a large family, and a wage-labor economy, which benefits from reduced fertility. Additionally, household size changes over the course of its life-cycle and shapes available economic opportunities. Here we argue that in mixed economies, fertility may reflect opportunities for livelihood diversity rather than simply responding to the restricted socioeconomic benefits of small families. While low fertility may in some cases have an economic benefit, low fertility can also limit the livelihood diversity of a household which is a key strategy for long-term economic success. We test this prediction with longitudinal data from a Maya community undergoing both a sustained decline in fertility and rapid integration into the market economy. Using household-level fertility, number of adults, and livelihood diversity at two time points, we find that household size is positively related to livelihood diversity, which in turn is positively related to household income per-capita. However, household size also has a negative association with income per capita. The results reflect a balancing act whereby households attempt to maximize the economic diversity with as few members as possible. Broadly, these results suggest that theories of fertility decline must account for how households pool resources and diversify economic activities in the face of increasing market integration, treating fertility as both an outcome and an input into economic and reproductive decision-making.